"Genetically Modified Lite" placates public but not activists. (22nd January 2014) - Hunter, Philip
<x xml:space="preserve">Abstract</x> New technologies that create genetically modified plants without transferring foreign genes may help to overcome public concerns, but they are unlikely to convince anti‐GM activists to give up the fight. <boxed-text content-type="graphic" id="embr201338365-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>